A comprehensive review on the application of emulsions as an alternative fuel for diesel engines. (February 2015) - Debnath, Biplab K.; Saha, Ujjwal K.; Sahoo, Niranjan
Abstract: Diesel engine is one of the most efficient and reliable energy conversion devices available till date. During the beginning of twentieth century, the plenty of low cost diesel have engrossed people to run diesel engines with diesel. However, after more than a century, the scenario has just been reversed. The frantic use of diesel has now led to a situation where the global fossil diesel storage may last merely for a few decades. As a result, the price of diesel has reached to a momentous height. This is coupled with the serious environmental pollution created by its burning. These facts have stimulated researchers around the globe to search for suitable, sustainable, renewable, and cheap alternative to diesel fuel, which is environmentally benign too. Among many solutions proposed, emulsified fuel is one of them, which comes under the fuel modification techniques. In this method, two or more mutually immiscible fluids are mixed together, which is expected to run a diesel engine and replicate its performance, combustion and emission characteristics. The most explored emulsified fuel in a diesel engine is the water in diesel emulsion. Alongside, the emulsions prepared with animal fat, methanol, ethanol and few studies with emulsified biodiesels have also been reported. The present paper attempts to accumulate most of these studies under a single shed. Efforts have been made to analyze the numerous studies on emulsified fuel both qualitatively and quantitatively. The paper starts giving an introduction to the types of emulsion, their characteristics, and the criteria of preparing an effective emulsion, followed by the review of their performance, combustion, emission and spray characteristics when run in a diesel engine. At the end, some of the significant points have been addressed based on the extensive review on the state-of-the-art literature, followed by some possibilities of future research.